Mimetic Study of Existential Reality in Sapardi Djoko Damono’s Sunyi Adalah Minuman Keras - Ratu Tria; Mardiah (Applied Linguistics: Innovative Approaches and Emerging Trends, 2025)
This study explores the mimetic representation of the protagonist's lived realities in Sapardi Djoko Damono’s novel, Sunyi Adalah Minuman Keras, utilizing M.H. Abrams' mimetic approach. The research employs a qualitative descriptive method, with data collected through intensive reading and note-taking techniques. Content analysis was applied to consolidate, sample, code, reduce, and describe the textual data. The findings reveal 30 data points categorized into four distinct aspects of the protagonist's, Rara's, lived realities. First, the familial reality highlights the tension where her mother pressures her regarding marriage and grandchildren. Second, the romantic reality illustrates a sudden breakup caused by her partner's demands to stop her online book-selling activities. Third, the social reality exposes the destructive nature of false rumors, such as pregnancy, spread by peers in her neighborhood and online. Finally, the social media reality emerges as the most dominant aspect, comprising 15 data points. It depicts Rara's deep sense of alienation, exhaustion, and entrapment within the digital world. Although she relies on social media to promote her work and interact with fans, it offers only an illusion of connection, surrounded by a "lonely crowd" making arbitrary comments. Ultimately, the study concludes that the protagonist's existence is overwhelmingly consumed by the monotonous and isolating nature of modern technology, reflecting a profound contemporary social reality.